Higher Anti-Cytomegalovirus Immunoglobulin G Concentrations Are Associated With Worse Neurocognitive Performance During Suppressive Antiretroviral Therapy. (1st March 2018) - Letendre, Scott; Bharti, Ajay; Perez-Valero, Ignacio; Hanson, Barbara; Franklin, Donald; Woods, Steven Paul; Gianella, Sara; de Oliveira, Michelli Faria; Heaton, Robert K; Grant, Igor; Landay, Alan L; Lurain, Nell; et al.
Abstract : HIV-infected adults are commonly coinfected with cytomegalovirus (CMV). In this cross-sectional, observational, exploratory study, higher CMV immunoglobulin G level in blood was associated with worse neurocognitive performance in adults living with HIV and taking suppressive antiretroviral therapy. Abstract: Background: Cytomegalovirus (CMV) has been linked to higher risk of cardiovascular disease and mortality. We aimed to determine if CMV is associated with neurocognitive performance in adults infected with human immunodeficiency virus (HIV). Methods: In this cross-sectional analysis, anti-CMV immunoglobulin G (IgG) concentrations in blood and CMV DNA copies in blood and cerebrospinal fluid (CSF) were measured in stored specimens of 80 HIV-infected adults who were previously assessed with a comprehensive neurocognitive test battery. Thirty-eight were taking suppressive antiretroviral therapy (ART) and 42 were not taking ART. A panel of 7 soluble biomarkers was measured by immunoassay in CSF. Results: Anti-CMV IgG concentrations ranged from 5.2 to 46.1 IU/mL. CMV DNA was detected in 7 (8.8%) plasma specimens but in no CSF specimens. Higher anti-CMV IgG levels were associated with older age ( P = .0017), lower nadir CD4+ T-cell count ( P < .001), AIDS ( P < .001), and higher soluble CD163 ( P = .009). Higher anti-CMV IgG levels trended toward an association with worse neurocognitive performance overall ( P = .059). This correlation was only present in those taking suppressive ART ( P = .0049). Worse neurocognitive performance remained associated with higher anti-CMV IgG levels after accounting for other covariates in multivariate models (model P = .0038). Detectable plasma CMV DNA was associated with AIDS ( P = .05) but not with neurocognitive performance. Conclusions: CMV may influence neurocognitive performance in HIV-infected adults taking suppressive ART. Future clinical trials of anti-CMV therapy should help to determine whether the observed relationships are causal.